2023
DOI: 10.1039/d2ta06965b
|View full text |Cite
|
Sign up to set email alerts
|

Effective perspiration is essential to uphold the stability of zero-gap MEA-based cathodes used in CO2 electrolysers

Abstract: The application of gas diffusion electrodes (GDEs) for the electrochemical reduction of CO2 to value-added products creates the possibility of achieving current densities of a few hundred mA cm–2. To...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It has also been shown recently that removing the surfactant changes the wettability of Ag NP solutions that will then deposit differently in a GDE setup. This overall crucially influences the stability of the catalysts, e.g., an excess of capping agent can lead to a blockage of the electrode micropores . As a last example, it was also shown in a RDE setup for the OER that small amount of PVP could stabilize Ir NPs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown recently that removing the surfactant changes the wettability of Ag NP solutions that will then deposit differently in a GDE setup. This overall crucially influences the stability of the catalysts, e.g., an excess of capping agent can lead to a blockage of the electrode micropores . As a last example, it was also shown in a RDE setup for the OER that small amount of PVP could stabilize Ir NPs …”
Section: Discussionmentioning
confidence: 99%
“…This overall crucially influences the stability of the catalysts, e.g., an excess of capping agent can lead to a blockage of the electrode micropores. 289 As a last example, it was also shown in a RDE setup for the OER that small amount of PVP could stabilize Ir NPs. 68 These results overall illustrate the benefits of surfactant-free NPs that lead to more active nanocatalysts but also enable the investigation of the effects of the surfactant to identify the minimal amount of additives needed to tune, for instance, stability or selectivity, whether these features result from tuning the active sites (e.g., having a role at the surface of the catalysts) or more engineering aspects (e.g., preparation of the catalysts in RDE or GDE).…”
Section: Simpler Synthesesmentioning
confidence: 97%
“…84 Thiols with different alkyl chain lengths 85 or 1-octadecanethiol 86 can be anchored on the Cu surface through coordination binding, allowing adjustment of the wettability of the GDE surface to manage water and CO 2 transport. Notably, Broekmann et al 87 found that residual or excess polymeric capping agents ( e.g. , polyvinylpyrrolidone and branched polyethylenimine) commonly used in catalyst synthesis procedures might induce GDE flooding, whereas monomeric citrate did not exhibit such a phenomenon.…”
Section: The Main Challenges and Solutions For Meamentioning
confidence: 99%
“…19,20 When the water coming from the cross-membrane H 3 O + or ECR is inadequate to dissolve and carry away the alkali salt, the salt precipitation will exacerbate the flooding of the GDE and lead to a decrease of ECR efficiency. 21,22 To further investigate the working mechanism of the modification layer, an anion ionomer of Nafion and a hydrophilic SiO 2 microsphere are employed to fabricate the modification layer for comparison, where the modification layer composed by the mixture of PTFE and Nafion is marked as PTFE-N, the electrode coated by SiO 2 and QAPPT is marked as SiO 2 -Q, and the electrode fabricated by coating the mixed ink of Ag, PTFE and QAPPT on carbon paper is marked as Mix (Fig. S7, ESI †).…”
mentioning
confidence: 99%
“…19,20 When the water coming from the cross-membrane H 3 O + or ECR is inadequate to dissolve and carry away the alkali salt, the salt precipitation will exacerbate the flooding of the GDE and lead to a decrease of ECR efficiency. 21,22…”
mentioning
confidence: 99%